2015
DOI: 10.1074/jbc.m114.601823
|View full text |Cite
|
Sign up to set email alerts
|

The Atlastin C-terminal Tail Is an Amphipathic Helix That Perturbs the Bilayer Structure during Endoplasmic Reticulum Homotypic Fusion

Abstract: Background:Atlastin is large GTPase that catalyzes the homotypic fusion of ER membranes. Results: In vitro and in vivo studies reveal that the C-terminal tail of Atlastin affects its function. Conclusion:The amphipathic C-terminal tail of Atlastin destabilizes lipid bilayers to promote membrane fusion. Significance: Describing the mechanism of Atlastin-mediated fusion is a critical step in our understanding of ER structure formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 33 publications
3
51
0
Order By: Relevance
“…Whereas Drosophila atlastin is an efficient fusogen in vitro (5,(31)(32)(33)(34)(35), the human atlastin proteins have been resistant to in vitro fusion analysis (36). We have confirmed that human atlastin-1 does not significantly promote membrane fusion in vitro (Fig.…”
Section: Biochemical Analysis Of Human Atlastin-1 and Human-drosophilsupporting
confidence: 64%
“…Whereas Drosophila atlastin is an efficient fusogen in vitro (5,(31)(32)(33)(34)(35), the human atlastin proteins have been resistant to in vitro fusion analysis (36). We have confirmed that human atlastin-1 does not significantly promote membrane fusion in vitro (Fig.…”
Section: Biochemical Analysis Of Human Atlastin-1 and Human-drosophilsupporting
confidence: 64%
“…In this case, GTP hydrolysis may be required to pull opposing membranes toward each other by catalyzing the transition from the open to the cross‐over helical conformation. Fusion of the closely juxtaposed membranes may then be further facilitated by disturbance of the lipids by TM‐regions and the amphipathic helix in the C‐terminal tail of atlastin . In addition, it has been suggested that the GTPase function may be used to recycle atlastin dimers in the cross‐over conformation back to the open conformation to allow new rounds of tethering across opposing membranes .…”
Section: Harnessing the Energy Of Gtp Hydrolysis For A Mechano‐chemicmentioning
confidence: 99%
“…ER membranes are first brought in close proximity by GTP-dependent formation and conformational transition of membrane-bridging Atlastin complexes. ER membranes are then destabilized by a C-terminal amphipathic helix which alters the lipid bilayer integrity [10,56,57]. Interestingly, similar membrane-proximal amphipathic helices, with a potential function in membrane destabilization and fusion, were also found in other fusion proteins such as the synaptic v-SNARE protein VAMP2 and the flavivirus protein E from the dengue virus [54,55,59], suggesting that amphipathic helices are a force to be reckoned with in membrane fusion events.…”
Section: Discussionmentioning
confidence: 96%
“…HR1 could mediate fusion like SNARE proteins do, that is, by assembling like a zipper (which would be a homotypic complex in the case of HR1) across the membranes destined to fuse, forcing their close apposition and lipid mixing [3][4][5][6][7][8]. Alternatively, HR1 could mediate fusion by perturbing the lipid bilayer structure, as recently shown for a C-terminal amphipathic fragment of the ER membrane fusion protein Atlastin [56,57]. Such perturbation could occur when HR1 interacts with the membrane in which it is anchored and/or when HR1 interacts with the opposing membrane.…”
Section: Discussionmentioning
confidence: 99%